Pengaruh Latihan Peregangan terhadap Gangguan Muskuloskeletal dan Kelelahan Kerja pada Pengerajin Ukiran Kayu di Desa Siangan - I Kadek Indra Partawiguna; Luh Gede Pradnyawati; Ni Wayan Rusni (Aesculapius Medical Journal, 2024)
[The Effects of Stretching Exercises on Musculoskeletal Disorders and Work Fatigue among Woodcarvers in Siangan Village] Stretching training or stretching exercise is an administrative action to limit the danger of mischief in the workplace. The danger risk can be experienced by workers is musculoskeletal disorders and work fatigue. The motivation behind this investigation was to decide the impact of stretching exercises on musculoskeletal disorders and work fatigue on woodcarvers at Siangan Village. The assessment of musculoskeletal disorders and work fatigue was measured using Nordic Body Map questionnaire with Likert scales and 30 Items also with Likert Rating Scales. The technique for this examination was quassy trial with One Groups Pretest-Posttest Design. The examples were chosen by purposive inspecting strategy, and information were analyzed using SPSS 22. The data were normally distributed (p = 0.081) so that it could be continued for analysis by T-Paired test. The outcomes were as per the following: the normal pre and post musculoskeletal disorders and work fatigue were 97.55 plus minus 9.55 ; 66.plus minus 3.77 and 59.53 plus minus 3.96 ; 5.06 plus minus 3.1 respectively. The conclusion could be drawn that there was critical impact of extending exercise on musculoskeletal disorders and work fatigue. It was recommended that ergonomics approach should be done to another labourS carvers.